Low‐calcium diet in mice leads to reduced gut colonization by Enterococcus faecium - Janetta Top; Antoni P. A. Hendrickx; Marleen T. J. vanAmpting; Kees vanLimpt; Jan Knol; Denise van deKamer; Johanna C. Braat; Marco Viveen; Malbert R. Rogers; Hans Kemperman; Rob J. L. Willems; Fernanda L. Paganelli (MicrobiologyOpen, 2019)
Abstract The aim of this study was to determine whether dietary intervention influenced luminal Ca2+ levels and Enterococcus faecium gut colonization in mice. For this purpose, mice fed semi‐synthetic food AIN93 were compared to mice fed AIN93‐low calcium (LC). Administration of AIN93‐LC resulted in lower luminal Ca2+ levels independent of the presence of E. faecium. Furthermore, E. faecium gut colonization was reduced in mice fed AIN93‐LC based on culture, and which was in concordance with a reduction of Enterococcaceae in microbiota analysis. In conclusion, diet intervention might be a strategy for controlling gut colonization of E. faecium, an important opportunistic nosocomial pathogen.